Critical Analysis of Pure Legal Theory in Contemporary Legal Development - Iskandar, Iskandar; Nurafifah, Diah; Permani, Intan (VARIA HUKUM, 2025)
Abstract: This study aims to examine and analyze the Pure Theory of Law developed by Hans Kelsen, focusing on both its strengths and weaknesses. Additionally, it assesses the extent to which this theory remains relevant and applicable in the context of contemporary law. The research employs a normative method with a conceptual approach to gain an in-depth understanding of the fundamental concepts within the Pure Theory of Law. This study is based on secondary data sourced from primary, secondary, and tertiary legal materials obtained through literature reviews and documentation. Data analysis is conducted using descriptive qualitative analysis. The findings indicate that Kelsen's theory provides a crucial foundation for the legal discipline, emphasizing that law should be understood as an autonomous normative system, independent of moral, social, and political values. However, in the face of ongoing social dynamics, such as globalization, digital technological advancements, and environmental crises, the Pure Theory of Law faces significant challenges due to its rigid and limited capacity to address the complexity of cross-border issues. While this theory remains vital as a basis for ensuring legal objectivity, its inability to accommodate social dynamics suggests that law requires a more flexible and adaptive approach.